2020
DOI: 10.1002/elsc.202000003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering in female pelvic floor reconstruction

Abstract: Pelvic organ prolapse is a common and frequently occurring disease in middle‐aged and elderly women. Mesh implantation is an ideal surgical treatment. The polypropylene mesh commonly used in clinical practice has good mechanical properties, but there are long‐term complications. The application of tissue engineering technology in the treatment of pelvic organ prolapse disease can not only meet the mechanical requirements of pelvic floor support, but also be more biocompatible than traditional polypropylene mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 131 publications
0
18
0
Order By: Relevance
“…Another way to trigger fibroblast proliferation and differentiation to myofibroblasts is by adding growth factors to the vaginal microenvironment. Epidermal growth factor (EGF) and basic fibroblasts growth factor (FGF) [ 91 ], or connective tissue growth factor (CTGF), as a downstream signal of TGF-b1, is a newly discovered growth factor that can stimulate the proliferation of fibroblasts and collagen deposition and can promote proliferation, migration, and differentiation of fibroblasts to myofibroblasts [ 92 ]. The endothelin-1 (ET-1) system regulates (myo)fibroblast contraction in wound healing.…”
Section: Role Of Fibroblasts In Wound Healing and Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to trigger fibroblast proliferation and differentiation to myofibroblasts is by adding growth factors to the vaginal microenvironment. Epidermal growth factor (EGF) and basic fibroblasts growth factor (FGF) [ 91 ], or connective tissue growth factor (CTGF), as a downstream signal of TGF-b1, is a newly discovered growth factor that can stimulate the proliferation of fibroblasts and collagen deposition and can promote proliferation, migration, and differentiation of fibroblasts to myofibroblasts [ 92 ]. The endothelin-1 (ET-1) system regulates (myo)fibroblast contraction in wound healing.…”
Section: Role Of Fibroblasts In Wound Healing and Tissue Regenerationmentioning
confidence: 99%
“…It is observed that low estrogen levels in women who undergo vaginal surgery affect the surgical outcome [ 34 ], and women who have continuously low estrogen levels exhibit delayed recovery due to impaired wound healing [ 93 ]. Therefore, adding estrogen to the surgical site promotes pelvic floor tissue repair by facilitating fibroblast proliferation and collagen synthesis [ 92 , 94 ]. These bioactive factors can also be useful at the implantation site of POP surgery as well as incorporating them in pelvic floor implants.…”
Section: Role Of Fibroblasts In Wound Healing and Tissue Regenerationmentioning
confidence: 99%
“…However, it can present low degradation and poor compatibility with tissues causing erosion, exposure, and infections. On the other hand, biological meshes, also known as implants from a natural source biomaterial, which are an extracellular matrix used on bone and cartilage reparation, were found as an alternative for the post-operation issues of the synthetic mesh despite having a poor mechanical property, causing the resurgence of the herniation [49,50]. The materials for natural source mesh are divided into two classifications.…”
Section: An Overview Of Tissue Engineering (Te)mentioning
confidence: 99%
“…In the specific case of mesh used in pelvic floor reconstruction, some of the natural sources of the materials needed are silk, cellulose and collagen type I, II and III. Thus, the use of scaffolds can be a better alternative for the repairing of the pelvic floor tissue [50]. Today, the TE in organs is aided by using organ printing, which involves three fundamental sequential steps: (i) pre-processing or development of 'blueprints' for organs, (ii) processing or actual organ printing, and (iii) postprocessing or organ conditioning and accelerated organ maturation [39].…”
Section: An Overview Of Tissue Engineering (Te)mentioning
confidence: 99%
“…Toward this goal, tissue engineering combining cells and scaffolds emerged as an alternative method for gynecological reconstruction and for that the selection of an appropriate scaffold is essential to provide tissue functionality providing an adequate anatomy (Sartoneva et al, 2018 ; Papadopulos et al, 2017 ; Wu et al, 2020 ), hence the importance of the approach involving PLGA/PIepox plus MSCs. Although this combination does not confer structural strength, it brings functionality and coating and must be combined with dilators in order to confer physical structure.…”
Section: Introductionmentioning
confidence: 99%